Perancangan Aplikasi Game Edukasi Pengenalan Hewan Dan Tanaman Langka Berbasis Android - Aliy Hafiz (Universitas Mitra Indonesia, 2021)
AbstractAndroid is an information technology that is currently being developed. Indonesia is listed as a country in Southeast Asia where the majority of its citizens use Android, namely 94% of users. The use of Android-based smartphones among children is now starting to increase. In general, the use of smartphones among teenagers is used to play games. Along with the development, various games have emerged that attract schoolchildren or students, one of which is an educational game on the introduction of rare animals and plants in Indonesia. Educational game applications are divided into 3 game stages, namely for early childhood from 3-7 years old, for elementary school (SD) children aged 7-12 years and general 13 years and over. Games for early childhood are with a game model that adjusts animal sounds and pictures, games for elementary school children are in the form of puzzles and quizzes while for the general public, they are in the form of puzzle games and quizzes with a time limit. From the results of direct analysis, observation and testing, educational games on the introduction of rare animals and plants can run well in accordance with the original purpose of making the application, with the application it can help in recognizing rare animals and plants in Indonesia which refers to the tendency of humans to be more receptive. information in the form of pictures and writing and at the same time the presence of this application can be a means of learning knowledge and playing that are effective, interesting, practical and educational.